Yahweh’s Consciousness: Isaiah 40-48 and Ancient Judean Historical Thought - Wilson, Ian Douglas (Vetus Testamentum, 2016)
This essay works toward three goals. First, it lays some groundwork for researching prophetic literature as a source for ancient Judean historical thought. Prophetic literature reveals a great deal about how ancient Judeans thought about and with their past, as it was represented in their literary repertoire. Second, it examines Isaiah 40-48, to see how this sort of second-order thinking about the past is on display in a particular passage of text. And third, it draws some preliminary conclusions about historical thought in this text and how it relates to historical thinking evident in other Judean literature.